Cariprazine maintenance treatment during pregnancy – a case report - Herold, Róbert; Tényi, Tamás; Herold, Márton; Tóth, Tünde (Frontiers in Psychiatry, 2024)
Data on reproductive safety of recently approved newer antipsychotics are limited.Here, we report a case vignette of a patient with schizophrenia treated with cariprazine during pregnancy. The patient became pregnant unexpectedly while taking medication. As a result of shared decision-making, the patient and her psychiatrist decided to continue the treatment, which proved to be protective against relapse and had no adverse effect either on the course of pregnancy or on the health of the newborn. Cariprazine maintenance treatment during pregnancy was found to be safe in our case.